2022
DOI: 10.1080/19490976.2022.2096328
|View full text |Cite
|
Sign up to set email alerts
|

Obesity enriches for tumor protective microbial metabolites and treatment refractory cells to confer therapy resistance in PDAC

Abstract: Obesity causes chronic inflammation and changes in gut microbiome. However, how this contributes to poor survival and therapy resistance in patients with pancreatic cancer remain undetermined. Our current study shows that high fat diet-fed obese pancreatic tumor bearing mice do not respond to standard of care therapy with gemcitabine and paclitaxel when compared to corresponding control diet-fed mice. C57BL6 mice were put on control and high fat diet for 1 month following with pancreatic tumors were implanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This resistance can be counteracted by SAM, which is typically produced by bacteria in lean diets, highlighting the influence of diet on chemotherapy effectiveness via gut microbiome adjustments. 307 Expanding on the theme of diet’s influence on chemotherapy effectiveness in pancreatic cancer, another study revealed that the microbiota-derived tryptophan metabolite indole-3-acetic acid (3-IAA) is enriched in patients responsive to chemotherapy. Through dietary manipulation of tryptophan, an increase in 3-IAA production enhances chemotherapy efficacy by disrupting cancer cell metabolic fitness via increased reactive oxygen species and reduced autophagy.…”
Section: Diet Changes the Gut Microbiome In Conjunction With Antitumo...mentioning
confidence: 99%
“…This resistance can be counteracted by SAM, which is typically produced by bacteria in lean diets, highlighting the influence of diet on chemotherapy effectiveness via gut microbiome adjustments. 307 Expanding on the theme of diet’s influence on chemotherapy effectiveness in pancreatic cancer, another study revealed that the microbiota-derived tryptophan metabolite indole-3-acetic acid (3-IAA) is enriched in patients responsive to chemotherapy. Through dietary manipulation of tryptophan, an increase in 3-IAA production enhances chemotherapy efficacy by disrupting cancer cell metabolic fitness via increased reactive oxygen species and reduced autophagy.…”
Section: Diet Changes the Gut Microbiome In Conjunction With Antitumo...mentioning
confidence: 99%
“…CD133 + cells tended to accumulate around adipocytes in pancreatic tumors. Kesh et al (2022) reported that conditioned media from patient-derived adipocytes increased CD133, Sox2, and Oct4 expression, which suggests that peritumoral adipocytes are part of the homing niche that maintains CD133 + population partially because of interleukins secretion such as IL6 [ 190 ].…”
Section: Cd133 Modulation By Microenvironmentmentioning
confidence: 99%
“…In one study, the gut microbe‐derived metabolite trimethylamine N‐oxide (TMAO), the main source of which is dietary choline, enhanced antitumor immunity in mice bearing pancreas tumors through the type I interferon pathway 38 . In the other study, obese mice were found to be resistant to chemotherapy, driven by an enrichment of gut bacteria producing queuosine, which upregulates the expression of antioxidant protein PRDX1 39 …”
Section: Preclinical Advancesmentioning
confidence: 99%